2011
DOI: 10.2527/jas.2011-4154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term corn by-product feeding on beef quality, strip loin fatty acid profiles, and shelf life

Abstract: The objective of this study was to evaluate the meat quality and shelf life of steaks from steers fed dried distillers grains with solubles (DDGS) or dried corn gluten feed (CGF) compared with soybean meal with corn (SBM) as a protein supplement from weaning to slaughter. Angus cross steers (n = 81; BW = 306 ± 26.1 kg) were randomly assigned to pens (n = 9) and fed a stocker diet of corn silage (75% of DM) with DDGS, CGF, or SBM and ground ear corn. After 84 d of stockering, 12 steers (BW = 397 ± 15.3 kg) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 30 publications
5
23
3
Order By: Relevance
“…There was no difference tenderness concentrations between treatments for any other aging and retail display period (data not presented). Segers et al (2011) reported that beef from cattle supplemented with 25% dried distillers plus solubles for 100 days was more tender than beef from cattle supplemented with soybean meal at 7 days of aging, and Depenbusch et al (2009) reported sensory overall tenderness ratings increased linearly as dietary level of distillers grains increased from 0% to 75%. Finally, Senaratne (2012) reported that beef from steers fed 30% WDGS tended (P < 0.10) to be more tender than beef from steers not fed a corn-only diet.…”
Section: Wbsf and Free Calcium Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no difference tenderness concentrations between treatments for any other aging and retail display period (data not presented). Segers et al (2011) reported that beef from cattle supplemented with 25% dried distillers plus solubles for 100 days was more tender than beef from cattle supplemented with soybean meal at 7 days of aging, and Depenbusch et al (2009) reported sensory overall tenderness ratings increased linearly as dietary level of distillers grains increased from 0% to 75%. Finally, Senaratne (2012) reported that beef from steers fed 30% WDGS tended (P < 0.10) to be more tender than beef from steers not fed a corn-only diet.…”
Section: Wbsf and Free Calcium Concentrationmentioning
confidence: 99%
“…Although many beef quality studies (Roeber et al 2005;Koger et al 2010;Mello et al 2012) on feeding distillers grains reported no differences in tenderness between control and treatments, a recent study (Senaratne 2012) revealed an intriguing phenomenon. Beef from steers fed 30% wet distillers grains plus solubles (WDGS) was more tender than beef from steers not fed WDGS, and this is not the first time that feeding distillers grains is reported to improve tenderness (Depenbusch et al 2009;Segers et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At 20% inclusion of DG, oleic acid did not differ, but decreased at 40% inclusion of DG (Koger et al, 2010). Segers et al (2011) compared ground corn-based diets with dried DG (DDG), corn gluten feed, or soybean meal as protein sources. Relative to steers consuming diets containing corn gluten feed or soybean meal, the concentration of oleic acid was decreased in longissimus lumborum steaks of steers fed DDG, whereas the stearic acid composition did not differ.…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%
“…It is well stablished that beef with higher concentration of PUFA is more likely to have increased lipid and myoglobin oxidation. Not surprisingly, detrimental effects on beef color under retail display have been reported, especially when distillers grains were included in finishing cattle diets at high rates LEUPP et al, 2009;SEGERS et al, 2011;MELLO et al, 2012;DOMENECH-PÉREZ et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A clear trend regarding the effects of feeding distillers grains on beef tenderness has not been established. Many authors have reported that the inclusion of distillers grains at different concentrations and feeding phases have no effect on meat tenderness measured via WBSF or sensory panel GILL et al, 2008;LEUPP et al, 2009;KOGER et al, 2010;SEGERS et al, 2011;MELLO et al, 2012). On the other hand, results from many other studies indicated that meat from cattle fed distillers grains was more tender than the meat from cattle fed a regular corn diet ALDAI et al, 2010;CHAO et al, 2017).…”
Section: Introductionmentioning
confidence: 99%